Evolution of prototyping in automotive engineering: a Comprehensive Study on the reliability of Additive Manufacturing for advanced powertrain components (Fracture and Structural Integrity, 2024)
Additive manufacturing (AM) could be used to reduce the production times of prototypes; however, further research is required to address metals structural parts. To obtain the correct properties, some relevant factors to be considered are the build volume, shape factor, and the need for specific heat treatments. This study aims to evaluate the reliability of AM prototypes applied at a new powertrain system developed to reduce vehicle emissions. Firstly, it was investigated the mechanical behavior, microstructure, and the effect of sample size and heat treatments on both specimens and prototypes made of AM 17-4PH steel. Finite Element Analysis (FEA) was performed to evaluate the structural resistance. Finally, the prototypes were produced, analyzed, and tested on a functional engine test bench to evaluate their reliability. The mechanical properties decreased with an increase in the sample volume. After heat treatment, the yield strength increased, due to the transformation of δ-ferrite in martensite and the reduction of retained austenite. The engine test bench was successfully completed. The conclusions set the basis for similar future applications of time-effective prototypes that can be dimensioned owing to appositely developed postprocesses that guarantee the required resistance.
Keywords: engine test bench; microstructure; Effect of shape; Mechanical properties; Additive manufacturing; automotive